PENGARUH MEDIA PEMBELAJARAN E-ATLAS DENGAN MOTIVASI BELAJAR SISWA SMA - Nur, Muhammad Rasyid (Universitas Negeri Yogyakarta, 2023)
E-Atlas was assessed using an assessment instrument in the form of a product quality assessment questionnaire by 1 media expert, 1 material expert, and paired t-test of 15 class XI students at SMA. The results of the E-Atlas of So (Scleroderma aurantium) Morphological Character assessment by media experts obtained an average score of 83.75% with quality in the feasible category, material experts scored 89.6% with quality in the very feasible category, and the biology teacher's assessment get a value of 96.25% with quality in the very decent category. The results of the paired t-test were found to be Sig.(2-tailed) of 0.000 0.05, so it can be concluded that there is a significant difference between the results of data collection before and after being given E-Atlas media.